A COMET ASSAY FOR CANDIDA GLABRATA INFECTION AND TREATMENT BY PENICILLIUM CHRYSOGENUM - DERIVED AgNPs - Teeba H. Mohammad, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The colonies of C. glabrata were described, which morphology of isolated on sabouraud dextrose agar with chloramphenicol. Biosynthesis of nanoparticles is of great importance since they are highly involved in various medical and biological applications. The current study aims to produce Penicillium chrysogenum - derived AgNPs to be used to treat Candida glabrata. Nanoparticles were formed, the results of which was observed through UV-visible spectrophotometry. Therefore, the surface morphology and particles size of AgNPs were assessed using the scanning electron microscope (SEM). The atomic force microscopy (AFM) confirmed that the average diameter of AgNPs was 18 nm which is appropriate to be used to deliver Penicillium chrysogenum to the Candida infected cells. The antifungal activity of AgNPs against C. glabrata was investigated in the serum of 15 mice. The mice were divided into four groups was examined after 21 days. A comet assay described procedure that sensitive measurement and permits reproducible of DNA repair and DNA damage using C. glabrara infection and treatment by Penicillium chrysogenum - derived AgNPs. This combination of assay with affected C. glabrara in DNA repaired and the extensive range of obtainable fungal molecular biology apparatuses can donate to light important devices of genome.